Pengaruh Pola Komunikasi dan Image Maker terhadap Organisasi Humas (Hubungan Masyarakat) - Sabrianti, Sabrianti; Putri, Khairani Kurniawan; setiyadi, Bradley (Universitas Batanghari Jambi, 2025)
This research aims to explore the influence of communication patterns and the role of image makers on the image of public relations organizations. The research method used is library study, with a focus on analyzing relevant literature from various academic and professional sources. This approach allows a thorough understanding of the factors that influence organizational communication and image formation. The results of this research conclude that transparent, open and consistent communication patterns have a positive impact on the image of a public relations organization. Clear and regular communication can strengthen the relationship between an organization and its audiences, build trust, and increase understanding of the organization's goals and values.